Integrating Statistical Techniques With The Reliability Engineering Methodology Of 'Failure Mode And Effects Analysis' For Continuous Improvement Of Manufacturing Processes. - Abdul Aziz, Zalina; Lim, Chee Peng; Cheow, Yin Leong (2003)

(untitled)
'Failure Mode and Effects Analysis' (FMEA) is a reliability engineering methodology for increasing the level of customer satisfaction in a company's products and services.